(untitled) (Research, Society and Development, 2020)
The objective was to evaluate the effects of different modified atmospheres on the packaging of sun-dried meat and their influence on the useful life. To this end, beef steaks of the hard topside type (Bíceps femoris) were cut, salted with 2.5% NaCl and packed in the following atmospheres: atmospheric air (CE-Ar); vacuum (CE-V); 100% CO2 (CE-ATM1); 50% CO2+ 50% N2 (CE-ATM2); 70% CO2+ 30% N2 (CE-ATM3); 30% CO2 + 70% N2 (CE-ATM4). The samples were evaluated for microbiological and physico-chemical quality. Meat packed in atmospheres with different CO2and N2 ratios had a useful life of up to 12 days, without significant variations between treatments, as to microbiological quality. Regarding the physicochemical characteristics, despite increasing the lipid oxidation in the meat, the atmospheres with different mixtures of CO2 and N2 used for packaging the meats presented the best quality characteristics. Therefore, according to this study, atmospheres modified with CO2 and N2 can be recommended as better alternatives to prolong the life of sun-dried meat.